MANAJEMEN PRODUKSI KONTEN INSTAGRAM @DBLSUB SAAT EVENT KFC DBL EAST JAVA SERIES 2022 OLEH PT. DBL INDONESIA DALAM MEMBANGUN CITRA SPORTAINMENT - Ramadhan, Achmad Rohman; S. I.Kom., M.A., Awang Dharmawan, (The Commercium, 2023)
This descriptive research with a qualitative approach is titled: "Content Production Management on Instagram @Dblsub during KFC DBL East Java Series 2022 Event by PT. DBL Indonesia." The research aims to understand the content production management on Instagram @dblsub during KFC DBL East Java Series 2022 event by PT. DBL Indonesia in building a sportainment image. The research method used is a descriptive qualitative method. In the research on Content Production Management on Instagram @Dblsub during KFC DBL East Java Series 2022 Event by PT. DBL Indonesia, some of the findings include: The content production management on Instagram @dblsub goes through four stages, namely planning, organizing, executing, and controlling. The production team prepares all aspects of content that align with the sportainment image. During the execution, several outputs in the form of high-engagement video reels were produced. To make it more attractive, the production team monitored and directly interacted with the Instagram audience. With effective production management, the Instagram followers of @Dblsub have reached 107,000.